Study of the dependence of the maximum normal stresses in the sections of thin-walled rods on the curvature of the bent axis in the longitudinal bending - A. S. Lichkovakha; B. A. Shemshura; S. A. Kuznetsov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The aim of the study is to determine the dependence of the normal stress on the radius of curvature of a flexible rod at different thicknesses. Method. A method was applied to determine the maximum stresses in a longitudinally compressed rod of high flexibility using elliptic integrals.Result. Modeling of a thin-walled longitudinally compressed rod was performed in the ANSIS calculation complex.Conclusion. The exact theory for calculating flexible rods allows you to determine the value of the axial force during longitudinal compression, at which the ends of the rod will close. When solving the problems of practical use of this type of rods, it is of interest to determine the maximum stresses, and at any stage of deformation, which makes it possible to choose the dimensional parameters of the elastic element and its material with greater accuracy.